PENGGUNAAN MEDIA KARTU BERGAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS II SDN 067 PEKANBARU - Sari, Eka Ramadhan; Kurniaman, Otang (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
This research is motivated by the low reading ability of 2nd grade students at SDN 067 Pekanbaru. The low reading ability of students is caused by the teacher not using learning media in learning so that the learning process becomes monotonous and students' abilities are different. One of the media that can be used to improve reading skills is the flashcard media. Media flashcard is a method of reading by using a card that contains pictures that are equipped with words. This study aims to improve the reading skills of 2nd grade students at SDN 067 Pekanbaru the use of flashcard. The research conducted was classroom action research with research subjects namely students in class 2 SDN 067 Pekanbaru totaling 24 people. The results of research on teacher activity increased at the first meeting of the  cycle I with a presentation of 70.83%, at the second meeting increased to 75%. Then in the cycle II increased again at the first meeting 83.33%, and the second meeting increased to 87.5%. Meanwhile student activity also increased, namely at the first meeting of the  cycle I having a percentage of 70.83% at the second meeting to 79.17%. Then at the first meeting the  cycle I increased to 87.5%, at the second meeting increased again to 91.67%. The results of increasing the reading ability of 2nd grade students at SDN 067 Pekanbaru, from the base score of 63.75, increased in the cycle I to 73.88 with a percentage of 15.89%, then in the cycle I again increased to 83.96 with a percentage of 31.70%